FROM MANUSCRIPT TO MODERNITY: THE DIGITAL REVOLUTION OF KITAB KUNING AND ITS IMPACT ON ISLAMIC STUDIES - Muhammad Faiq Hirzulloh; Kholis Ali Mahmudi (Universitas Islam Negeri Mataram, 2026)
The transition from handwritten manuscripts to digital formats has profoundly reshaped Islamic scholarship in Indonesia. This study examines how digitisation affects access to and interpretation of the Kitab Kuning within contemporary educational policy frameworks. Using a qualitative approach, the research identifies a movement away from reliance on physical texts toward digital validation processes. Findings reveal that digitisation not only alters information storage methods but also impacts scholarly authority and learning practices in pesantren. At the same time, digital adoption introduces challenges such as digital‑literacy gaps, fragmentation of religious authority, and the risk of losing the contextual nuances embedded in the original manuscripts. The article proposes a policy framework that balances tradition preservation with technological adoption and recommends enhancing students’ digital competencies and standardising academic repositories. This research enriches the discourse of digital humanities in Islamic studies and offers practical recommendations for policymakers, educators, and researchers.